ChemInform Abstract: A Formal anti‐Markovnikov Hydroamination of Allylic Alcohols via Tandem Oxidation/1, 4‐Conjugate Addition/1, 2‐Reduction Using a Ru Catalyst. Issue 34 (August 2015) - Nakamura, Yushi; Ohta, Tetsuo; Oe, Yohei
Abstract 24 examples